Academic rankings and pluralism: The case of Brazil and the new version of Qualis - Ian Coelho de Souza Almeida; Rafael Galv\~ao de Almeida; Lucas Resende de Carvalho (EconomiA, 2018)
The paper approaches the theme of the relatively higher level of pluralism in Brazilian economics, when compared to other countries, from a bibliometric approach. Considering the Qualis as an instrument of great impact in the research of the Brazilian graduate education centers, mainly because of its impact in the CAPES evaluation of the centers, we analyze the abrupt change in the journal ranking that occurred in 2016. Before presenting it, we first focused in understanding the metrics that are part of the Qualis, and how relevant the biases from other indexes than the Impact Factor are. Afterwards, we present a review of the national literature concerning the academic production in economics, showing how some problems of incentives and structure still persist. We, then, present our results: we found out that the increase of journals in the higher strata of the Qualis without a research agenda bias, and with a great inclusion of specialized sub-fields of the discipline. Besides, the impact that this change will cause in the 2017 CAPES' evaluation cannot be seen as favoring centers by their division in mainstream and non-mainstream. Having this in mind, we argue that the modifications maintain incentives to pluralism, besides correcting many problems in the ranking.
Keywords: A23; A14; B00; 330; Academic production; Bibliometrics; Heterodox economics; Mainstream economics; Pluralism; Qalis